Application of XBeach model to study sedimentation of Lach Van river mouth : Major Coastal Engineering and Management: Code 62-58-02-03 - Nguyen, Quoc Anh (Thuy Loi University, 2020)
The study aims to simulate the geomorphologic change and predict bathymetry evolution of Lach Van river mouth using the XBeach 2D model.